Effectiveness of Nifedipine in Preterm Labour Suppression - Sadiq Jan, Ayesha Naeem, Sughra Abbasi, Zubda Anwar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To understand the safety and effectiveness of nifedipine as a tocolytic agent in preterm labor. Study Design: A Quasi-experimental study. Place and Duration: The study was held in the Obstetrics and Gynecology Department of Riphah International Hospital Rawalpindi for one-year duration from January 2021 to December 2021. Methodology: 90 singleton pregnancies with cervical dilatation less than 3 cm and intact membranes with preterm labour occurred between 28-34 weeks of pregnancy were included and nifedipine was given as a tocolytic agent. Results: This study was performed on 90 patients, 55(61.1%) of whom were primigravida and 35(38.9%) were multiparty. 27.1 + 5.2 years was the mean age of patients (range 20 to 45 years), 74.4% were unbooked patients compared to 25.6% were booked patients. The tocolysis was obtained successfully in 76.7% of patients. The number of days obtained in delayed delivery was analyzed (Table 1B). Overall achievement in postponing delivery over 2 and 3 days is 76.7% (69/90). 21 patients (23.3%) were considered treatment failures. Of the patients who failed treatment (21/90), 18 patients gave birth in one day and 3 patients in two-days. The mean delay in delivery <2 days was 1.0 + 0.3 days, while the delay >2 days was 4.31 + 9.0, which is statistically important at> p 0.008. The mean heart rate prior to treatment was 83.0 + 5.0, afterwards to treatment with nifedipine it was 92.0 + 5.0, indicating a difference of 9 bpm: statistically insignificant in heart rate. Conclusion: Nifedipine was effective in suppressing preterm delivery and delaying delivery long enough to achieve therapeutic effect and transfer the mother to the 3rd degree care unit.